2019
DOI: 10.1016/j.sjbs.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of silver nanoparticles by using of the marine brown alga Padina pavonia and their characterization

Abstract: Silver nanoparticles (AgNPs) are gaining considerable importance due to their attractive physicochemical properties for many applications. In the present study, (Ag NPs) were synthesized by the reduction of aqueous solutions of silver nitrate (AgNO3) with powder and solvent extracts of Padina pavonia (brown algae). The obtained nanoparticles exhibited high stability, rapid formation of the biogenic process (2 min -3 h), small size (49.58–86.37 nm) (the diameter of formed nanoparticles was measured by TEM and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(40 citation statements)
references
References 21 publications
3
37
0
Order By: Relevance
“…After the reduction of AgNO 3 , the increases in intensity at 1384.27 cm −1 [6] signified the involvement of nitro compounds into NO 2 aliphatic amines [31] in the reduction process. The strong spectral band at 1384.27 cm −1 and 1023.91 cm −1 [11] as observed in Fig. 5c was interpreted for the identification of organic compounds adhering to the silver nanoparticles synthesized as shown in Table 1.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 80%
See 1 more Smart Citation
“…After the reduction of AgNO 3 , the increases in intensity at 1384.27 cm −1 [6] signified the involvement of nitro compounds into NO 2 aliphatic amines [31] in the reduction process. The strong spectral band at 1384.27 cm −1 and 1023.91 cm −1 [11] as observed in Fig. 5c was interpreted for the identification of organic compounds adhering to the silver nanoparticles synthesized as shown in Table 1.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 80%
“…Silver ions (Ag + ), are engaged in the formulation of dental resin composites, bone cement, ion exchange fibers and coatings for medical devices since its being an antibacterial component [4]. Recently, studies conducted have shown that silver nanoparticles exhibit strong inhibition and serve as a protective barrier for most of the microorganism, for example, grampositive bacteria, gram-negative bacteria, drug-resistant bacteria, viruses, fungus, and even some of the pathogens [6,10] Studies have shown that the silver nanoparticles which can be synthesized using algae are cost-effective and environmentally friendly as they do not require toxic chemicals in the process [11]. The availability of marine algae throughout the year and easy accessibility to harvest them encourages the researchers' interest on marine algae-mediated biosynthesis of silver nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Silver nanoparticles have potential as an alternative to antibacterial drugs due to promising effects against MDR bacteria in vivo and in vitro. 24,25 Silver nanoparticles have been shown to exert a significant inhibitory activity toward gram-negative and gram-positive bacteria due to their small sizes and large surface area to volume ratios, which facilitate the extensive interactions between SNPs and bacteria. 26 Currently, the scientific community is progressively developing to develop and discover novel therapeutic agents to treat cancer that is considered as the second leading cause of death worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction mixture contained 1 g of S. obliquus and S. platensis dry matter and 50 mL of 4mM AgNO3 aqueous solution, and incubated at 30 ͦ C for 24h with the continuous stirring condition. The change in color was envisaged as the evidence of bioreduction (Meena et al, 2007;Abdel-Raouf et al, 2018).…”
Section: Biosynthesis Of Agnps By the Algal Powdermentioning
confidence: 99%